the Falsafah Pepali Pitu Sunan Drajat dalam Perspektif Tasawuf: Studi Komparatif dengan Konsep Bidayah al-Hidayah Imam al-Ghazali - Angkara, Barda; Khasbullah; Kusno, Moh. (Jurnal Studi Multidisiplin Qomaruna, 2025)
This study examines Pepali Pitu of Sunan Drajat as a philosophical teaching that embodies wisdom, social ethics, and spirituality within the framework of Sufism, and compares it conceptually with Bidayah al-Hidayah by Imam al-Ghazali. This research employs a library research method with a descriptive-analytical approach to explore the similarities and differences in the spiritual journey structure of both teachings. The findings reveal that both Pepali Pitu and Bidayah al-Hidayah emphasize the spiritual stages of human life through the concepts of takhalli, tahalli, and tajalli, focusing on self-purification, moral development, and closeness to God. The main difference lies in their approach: Sunan Drajat conveys Sufi values through local Javanese cultural symbols, while al-Ghazali formulates them systematically within the classical Islamic scholarly tradition. These findings highlight that Sufism remains relevant as a moral and spiritual guide that is adaptable to both local and universal contexts. This study is limited by its conceptual scope and does not empirically examine how these values are practiced in contemporary Muslim communities. Therefore, future research is recommended to investigate the practical implementation of Pepali Pitu and Bidayah al-Hidayah, especially in character education and cultural-based Islamic propagation.